Purification of Sufism According to Hamka - Kaplan, Muhammed Nur; Zarkasyi, Arif Afandi (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2024)
This research investigates Hamka's concept of Modern Sufism as a significant effort to purify and reform traditional Sufism. The study begins by exploring the historical context of Sufism in Indonesia, where it played a pivotal role in the dissemination of Islam but was later influenced by mystical, materialistic, and hedonistic elements. These influences often deviated from the foundational principles of Islam, necessitating a return to its purest form. The study adopts a descriptive and inductive research design, analyzing Hamka's seminal works. The research focuses on Hamka's critique of practices like saint veneration, excessive grave visitation, and misinterpretations of concepts like waḥdah al-wujūd. Hamka's approach emphasizes tawḥīd (the Oneness of God) as a cornerstone of Sufi practice, advocating for a direct and immanent relationship with Allah without intermediaries. The findings reveal that Hamka redefined wealth and poverty in Sufism. Wealth, according to Hamka, is not inherently negative but should be seen as a trust from Allah, to be used for good deeds and social welfare. True poverty, on the other hand, lies in detachment from material possessions, even amidst abundance, reflecting the principle of zuhd (asceticism). Furthermore, Hamka's Modern Sufism rejects hedonistic tendencies by promoting self-control and prioritizing social engagement as essential aspects of a successful Sufi life. The study concludes that Hamka’s Modern Sufism bridges spirituality with societal needs, offering a dynamic and pragmatic framework for addressing the spiritual crises of modern society. His approach not only restores Sufism to its monotheistic roots but also ensures its relevance in contemporary contexts, balancing worldly and spiritual aspirations.